Foot Print : the Tracks of Shoes in Fashion - Bruloot, Geert; Judah, Hettie; Espinosa, Dodi (Tielt : Lannoo Publishers, 2015)
Vivier, Roger ; Golbin, Pamela ; Ferragamo, Salvatore ; Ferragama, Wanda ; Blahnick, Manolo ; Cox, Patrick ; Gaultier, Jean Paul ; de Havilland, Terry ; Kumagaï, Tokio ; Clergerie, Robert ; Vandevorst, A.F. ; Demeulemeester, Ann ; Margiela, Martin ; Persoons, Jurgi ; Bikkembergs, Dirk ; Van Noten, Driees ; Jones, Stephen ; Simmons, Tabitha ; Gigli, Romeo ; Alaïa, Azzedine ; Lang, Helmut ; Kirkwood, Nicholas ; Hardy, Pierre ; Simons, Raf ; Zanotti, Giuseppe ; Prada ; Rossi, Gianvito ; WeberHodelFeder
boek